The Role of the SIMPD (Official Travel Management Information System) Application in Facilitating Monitoring of Official Travel within the Secretariat of the East Java Provincial DPRD - Mudiono Mudiono; Aris Sunarya; Amirul Mustofah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
The Official Travel Management Information System (SIMPD) is a digital-based application developed to support the management and monitoring of official travel activities within the Secretariat of the Regional People's Representative Council (DPRD) of East Java Province. This study aims to analyze the role of the SIMPD application in facilitating ease of monitoring official travel within the Secretariat of the DPRD of East Java Province. The research employs a qualitative descriptive approach with data collection conducted through observation, interviews, literature study, and documentation. The conceptual framework used in this study is the policy implementation theory proposed by Edwards III, which reviews four key aspects: communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of SIMPD has generally contributed positively to the management and monitoring of official travel, improving transparency, efficiency, and accountability. However, several challenges remain, including inconsistent socialization, limited human resource capacity, and the need for stronger inter-agency coordination. This study recommends strengthening digital governance infrastructure, increasing the number of trained operators, and enhancing coordination between relevant agencies to optimize SIMPD implementation